2001
DOI: 10.4049/jimmunol.167.6.3099
|View full text |Cite
|
Sign up to set email alerts
|

Human Endothelial-Cell Specific Molecule-1 Binds Directly to the Integrin CD11a/CD18 (LFA-1) and Blocks Binding to Intercellular Adhesion Molecule-1

Abstract: ICAMs are ligands for LFA-1, a major integrin of mononuclear cells involved in the immune and inflammatory processes. We previously showed that endothelial cell specific molecule-1 (ESM-1) is a proteoglycan secreted by endothelial cells under the control of inflammatory cytokines. Here, we demonstrate that ESM-1 binds directly to LFA-1 onto the cell surface of human blood lymphocytes, monocytes, and Jurkat cells. The binding of ESM-1 was equally dependent on Ca2+, Mg2+, or Mn2+ divalent ions, which are specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
218
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 37 publications
5
218
1
4
Order By: Relevance
“…We chose 13 genes for detailed validation based on affinity reagents that could reliably identify the protein products. Most of these genes play important roles in processes that are in fact vital for tumor growth, such as regulation of endothelial permeability, leukocyte extravasation, 26 cell adhesion, 27,28 extracellular matrix degradation [29][30][31] and metastasis. 32 Nine of the genes (ADAM12, CDCP1, CSPG2, EGFL6, ESM1, FLJ46072, LGALS3BP, ST14 and TSG6) exhibited higher expression in ovarian cancer relative to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We chose 13 genes for detailed validation based on affinity reagents that could reliably identify the protein products. Most of these genes play important roles in processes that are in fact vital for tumor growth, such as regulation of endothelial permeability, leukocyte extravasation, 26 cell adhesion, 27,28 extracellular matrix degradation [29][30][31] and metastasis. 32 Nine of the genes (ADAM12, CDCP1, CSPG2, EGFL6, ESM1, FLJ46072, LGALS3BP, ST14 and TSG6) exhibited higher expression in ovarian cancer relative to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte Function-associated Antigen 1 (LFA1) and Very Late Antigen 4 (VLA4) Blocking Experiment-Calcein-labeled U937 cells were incubated in the presence of anti-integrin ␣ L (anti-LFA1, 4 g/ml; clone HI111, Biolegend) or anti-integrin ␣ 4 (anti-VLA4, 4 g/ml; clone 2B4, R&D Systems) in ice-cold RPMI medium for 1 h. These antibodies were previously demonstrated as blocking interactions between LFA1 and ICAM1 (26) or between VLA4 and VCAM1 (27). These cells were then used in monocyte adhesion assays as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that endocan actively participates in the interaction of endothelial cells and leukocytes. The study by Béchard et al (3) confirmed that endocan acts on physical function or has a specific interaction with the LFA-1 integrin extracellular domain of Jurkat cells that rely on a combination of divalent cations, which are specificity, saturation and temperature sensitive. The binding sites of endocan and LFA-1 to ICAM-1 are different.…”
Section: Classic Function Of Endocanmentioning
confidence: 75%
“…IdoA is an important component of the functional structure of endocan. In cancer patients, patients with sepsis and tissue samples of healthy volunteers, serum protein endocan is present in the form of a polysaccharide (1)(2)(3)(4). Studies of the HUVEC vascular endothelial cell model show that the endocan expression level is extremely low, which cannot meet the requirements of scientific research (4).…”
Section: Introductionmentioning
confidence: 99%